Fabricación de una película comestible de alginato de sodio (2023)
The main objective of this degree project is to demonstrate that a sodium alginate-based biofilm can extend the postharvest life of a fruit as delicate as strawberries through the casting method for the production of the biofilm. To make the biofilm, sodium alginate was combined with other natural polymers such as pectin and aloe vera. The films were formulated varying the alginate - aloe vera and alginate - pectin ratio from 80:20 to 50:50, glycerol was added as a plasticizer in concentrations of 2 and 5% v/v. The formed films were characterized by physicochemical tests such as solubility, moisture percentage and the weight supported by each membrane.